2018
DOI: 10.1108/jmtm-02-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Adopting additive manufacturing in SMEs: exploring the challenges and solutions

Abstract: Purpose Adopting additive manufacturing (AM) can be challenging, especially in small- and medium-sized enterprises (SMEs) and as part of the supply chains of larger firms. The purpose of this paper is to explore SMEs’ perspectives on the adoption of AM in their specific supply chain positions. The paper develops new knowledge on the challenges SMEs face across the supply chain and the actions they need to promote the adoption of AM. Design/methodology/approach An exploratory interview-based research design i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 37 publications
6
118
1
Order By: Relevance
“…Interpretation of factor weights Market demand, the highest-ranking factor of this study, refers to current and forecasted market demand. Currently, AM technologies cater to the demands of various small market Luomaranta, 2018). It would certainly be easier for AM companies if there was a better understanding of the technology in the market and if they could cater to a strong demand.…”
Section: Robustness Of the Resultsmentioning
confidence: 99%
“…Interpretation of factor weights Market demand, the highest-ranking factor of this study, refers to current and forecasted market demand. Currently, AM technologies cater to the demands of various small market Luomaranta, 2018). It would certainly be easier for AM companies if there was a better understanding of the technology in the market and if they could cater to a strong demand.…”
Section: Robustness Of the Resultsmentioning
confidence: 99%
“…Currently, investment in AM production capacity and knowledge is expensive and risky for most organisations (Thomas 2016;Weller, Kleer, and Piller 2015). This particularly holds because of fast technological advancements and rapidly changing market dynamics (Garmulewicz et al 2018;Martinsuo and Luomaranta 2018). Pooling AM capacity across organisations might lessen associated cost and risk but increase the organisational effort (Togwe, Eveleigh, and Tanju 2019).…”
Section: Costsmentioning
confidence: 99%
“…These results showed that halal agro-food SMEs are facing similar challenges to adopting technologies like other SMEs. Therefore, it is very important to remove these challenges as suggested by Marasini et al (2008); Martinsuo and Luomaranta (2018) to improve the adoption of technology among SMEs.…”
Section: Iot Challenges Among Halal Agro-food Smesmentioning
confidence: 99%